Dinamika Komunikasi dalam Hubungan Toksik di Kalangan Remaja di Kota Bandung - Fadia Annisa Rezkita; Jeanny Maria Fatimah; Tuti Bahfiarti (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2026)
This study examines the dynamics of communication in toxic relationships among adolescents in Bandung, focusing on possessiveness, restrictions on social interaction, and verbal and physical abuse that occur in such relationships. The purpose of this study is to understand the patterns of communication in toxic relationships, their impact on mental health, and the dynamics of forgiveness that occur in such relationships. The research method used was a qualitative approach with in-depth interviews with adolescents involved in toxic relationships. The results show that patterns of possessiveness and social control are the main characteristics of toxic relationships, while verbal and physical abuse reduce the victim's self-confidence and mental health. The repeated process of forgiveness worsens emotional dependence and prolongs the harmful relationship. These findings have important implications for the development of psychological interventions for adolescents.